Eksistensi Falsafah Adat Berbasis Islam di Nusantara:Telaah Konsep Adat Basandi Syarak, Syarak Basandi Kitabullah - Revi Ardila; Erica Asnishalima; Yunda Fitria Ningsih; Hoktaviandri (Jurnal Reflektif, 2026)
The relationship between adat and Islamic sharia is a distinctive phenomenon of cultural acculturation in the Indonesian archipelago, where the philosophy of Adat Basandi Syarak, Syarak Basandi Kitabullah (ABS-SBK) among the Minangkabau people stands as one of the most well-established examples of this integration. However, studies that place ABS-SBK in a comparative perspective with Islam-based adat philosophies in other regions remain relatively limited. This study aims to examine the existence of the ABS-SBK concept as the primary philosophy of the Minangkabau people and to compare it with Islam-based customary philosophies in various regions of the Indonesian archipelago, such as Gorontalo, Aceh, Riau Malay, Bugis-Makassar, and Banjar. The study employs a narrative literature review method by analyzing primary and secondary sources, including customary texts, studies on customary law, and relevant academic literature. The results indicate that although there are differences in formulation, terminology, and institutional characteristics, all of these Islamic-based customary philosophies share the same underlying pattern: they position Islamic Sharia as the highest source of values that underpin customary norms. This study concludes that the pattern of adat-sharia integration is universal but manifests in diverse local formulations, thereby enriching the treasury of local Islamic wisdom in the Nusantara and serving as a relevant model for contemporary religious moderation.